A Bibliometric Analysis of Sustainable Development Goals (SDGs) Through the Lens of Maqasid Shariah Tafsir - Elbanna, Mariam; Wadi, Munshid Falih; Radiamoda, Anwar M.; Matsuyama, Yohei; Ishak, Mohamad Haeqal Bin (QiST: Journal of Quran and Tafseer Studies, 2025)
This study aims to conduct a bibliometric analysis of research intersecting the Sustainable Development Goals (SDGs) and Maqasid Shariah Tafsir, with a focus on using VOSviewer software to visualize research patterns and trends. The analysis spans the last decade, exploring publication trends over time, influential journals, prolific authors, and the most productive countries and institutions in this field. The results show a significant growth in research integrating Maqasid Shariah principles, focusing on the preservation of religion, life, intellect, lineage, and wealth, with the 17 SDGs, such as poverty eradication, quality education, and environmental sustainability. The analysis also highlights key research keywords and emerging themes, such as ethical governance, social justice, and economic sustainability. Using VOSviewer helps create visual maps of research networks, providing insights into relationships between authors, institutions, and keywords. The analysis reveals the prominent role of specific countries and institutions that support research in this area, emphasizing the importance of interdisciplinary collaboration in advancing this discourse. The study provides a foundation for understanding the relationship between Shariah principles and the SDGs, opening avenues for future research aimed at enhancing the use of Islamic values to address global sustainability challenges. The findings assist policymakers and researchers in identifying research gaps and collaboration opportunities for greater impact.